2020
DOI: 10.1186/s12888-020-02702-0
|View full text |Cite
|
Sign up to set email alerts
|

A psychometric approach to assessments of problematic use of online pornography and social networking sites based on the conceptualizations of internet gaming disorder

Abstract: Background: The problematic use of online gaming, social networking sites (SNS) and online pornography (OP) is an evolving problem. Contrary to the problematic use of SNS and OP, Internet gaming disorder (IGD) was included in the new edition of the Diagnostic and statistical manual of mental disorders (DSM-5) as a condition for further study. The present study adapted the criteria for IGD to the problematic use of SNS and OP by modifying a validated questionnaire for IGD (Internet Gaming Disorder Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The current study found 12.5% prevalence of problematic pornography use among participants. Mennig et al 19 found that 7.1% participants have problematic use of pornography. Dwulit et al 20 in a cross-sectional study among Polish University students found 12.2% prevalence of self-perceived pornography addiction.…”
Section: Problematic Pornography Usementioning
confidence: 99%
“…The current study found 12.5% prevalence of problematic pornography use among participants. Mennig et al 19 found that 7.1% participants have problematic use of pornography. Dwulit et al 20 in a cross-sectional study among Polish University students found 12.2% prevalence of self-perceived pornography addiction.…”
Section: Problematic Pornography Usementioning
confidence: 99%
“…The reliability of the scale was 0.84. 15 This scale shows satisfactory psychometric property for the current study using Cronbach's alpha (0.74).…”
Section: Methodsmentioning
confidence: 69%
“…The tendency of SPP-OP use was assessed using the OPDQ. The OPDQ is a version of the Internet Gaming Disorder Questionnaire (IGDQ; Petry et al, 2014 ) that was modified to assess SPP-OP use (Mennig et al, 2020 ) and consists of nine items, with a dichotomous response format of “no” (0) and “yes” (1). The items are modelled on the DSM-5 criteria for IGD and a total score is calculated by adding the responses (score range: 0–9).…”
Section: Methodsmentioning
confidence: 99%
“…An example item is: “Do you feel that you should spend less time watching OP but are unable to cut back on the amount of time you spend watching OP?”. The psychometric evaluation indicated that this is a useful instrument for the questionnaire-based assessment of problematic use of OP (Mennig et al, 2020 ). The OPDG showed good internal consistency with ω ordinal = 0.88.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation